2007
DOI: 10.1192/bjp.bp.106.021402
|View full text |Cite
|
Sign up to set email alerts
|

Psychological treatments for chronic post-traumatic stress disorder

Abstract: The first-line psychological treatment for PTSD should be trauma-focused (TFCBT or EMDR).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

23
451
6
22

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 786 publications
(510 citation statements)
references
References 44 publications
(52 reference statements)
23
451
6
22
Order By: Relevance
“…Besides significantly compromising a person’s well-being and impairing psychosocial and occupational functioning (Olatunji, Cisler, & Tolin, 2007), PTSD also places a heavy burden on society (Olesen, Gustavsson, Svensson, Wittchen, & Jönsson, 2012). Although evidence-based interventions for PTSD are available (Bisson et al, 2007), studies examining interventions to prevent PTSD’s onset have not been encouraging, and the majority of these studies have shown that they are ineffective or may even increase PTSD symptoms (e.g. psychological debriefing; Rose, Bisson, Churchill, & Wessely, 2002; Sijbrandij, Olff, Reitsma, Carlier, & Gersons, 2006; but see Rothbaum et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Besides significantly compromising a person’s well-being and impairing psychosocial and occupational functioning (Olatunji, Cisler, & Tolin, 2007), PTSD also places a heavy burden on society (Olesen, Gustavsson, Svensson, Wittchen, & Jönsson, 2012). Although evidence-based interventions for PTSD are available (Bisson et al, 2007), studies examining interventions to prevent PTSD’s onset have not been encouraging, and the majority of these studies have shown that they are ineffective or may even increase PTSD symptoms (e.g. psychological debriefing; Rose, Bisson, Churchill, & Wessely, 2002; Sijbrandij, Olff, Reitsma, Carlier, & Gersons, 2006; but see Rothbaum et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…EMDR is an evidence-based psychological treatment that is frequently used and effective in post-traumatic stress disorder (PTSD) and its affiliated symptoms (Bisson et al, 2007; Bradley, Greene, Russ, Dutra, & Westen, 2005; Seidler & Wagner, 2006). Desensitization and reprocessing of memories and images that contribute to the symptoms, such as events in which the tinnitus acquired negative meaning, may reduce tinnitus distress.…”
Section: Introductionmentioning
confidence: 99%
“…Serious health problems often co-occur with PTSD, such as chronic pain and circulatory and musculoskeletal symptoms (Pacella, Hruska, & Delahanty, 2013). Consequently, PTSD has a large impact on the social and occupational functioning of patients (Bisson et al, 2007). …”
mentioning
confidence: 99%
“…Trauma-focused cognitive behavioural therapy (TF-CBT) and eye movement desensitization and reprocessing therapy (EMDR) are demonstrably the most efficacious treatment methods for PTSD to date and are recommended as treatments of choice in several guidelines (Bisson et al, 2007; National Institute of Clinical Excellence [NICE], 2015). However, several reviews and meta-analyses have shown that these treatments have large dropout and considerable non-response rates.…”
mentioning
confidence: 99%